People or Property Legal Contradictions, Climate Resettlement, and the View from Shifting Ground - Jerolleman, Alessandra (Springer Nature, 2024)
This open access book explores the intersection of property law, relocation, and resettlement processes in the United States and among communities that grapple with migration as an adaptation strategy. As communities face the prospect of relocating because of rising seas, policy makers, disaster specialists, and community leaders are scrambling to understand what adaptation pathways are legally possible. While in its ideal application, law functions blindly and without variation, the authors find that legal contradictions come to bear on resettlement processes and place certain communities further in harm's way. This book will unearth these contradictions in order to understand why successful community-based resettlement has presented such a challenge to communities that are experiencing increasing land deterioration as a result of climate change.